Implementing DevOps with Microsoft Azure - Soni, Mitesh; Soni, Mitesh (Packt Publishing, 2017)
Accelerate and Automate Build, Deploy, and Management of applications to achieve High Availability.About This BookThis guide highlights tools that offer development and deployment environments for application servicesSecure and continuously monitor your web application in order to make it highly availableUse Visual Studio Team Services for Continuous Integration and Continuous Development to expedite your application life cycle management processUse Microsoft Azure App Services (Azure Web Apps / Azure Websites), PaaS offering from Microsoft to deploy web applicationWho This Book Is ForThis book is for DevOps engineers, system administrators, and developers (.net) who want to implement DevOps for their organization. You do not need to have any knowledge of VSTS or Azure App Services (Azure Web Apps / Azure Websites).What You Will LearnExplore the features of PaaS and aPaaS in DevOpsUse Visual Studio Team Services (VSTS) to manage versions of code and integrating VSTS with Eclipse IDEUnderstand and configure Continuous Integration in VSTSReview Unit Test Execution for Automated TestingCreate different environments that can be used to continuous deploy a web applicationConfigure Roll-based Access to enable secure access for Azure Web AppsCreate and configure the App Service Environment to enhance securityUnderstand the execution of the end-to-end automation processConduct Performance Testing using JMeterDiscover the different monitoring options available in Microsoft Azure PortalIn DetailThis book will teach you all about the Visual Studio Team Services and Microsoft Azure PaaS offerings that support Continuous Integration, Continuous Delivery, Continuous Deployment, and execution in the cloud with high availability, disaster recovery, and security.You will first be given a tour of all the concepts and tools that Microsoft Azure has to offer and how these can be used in situations to cultivate the DevOps culture. You'll be taught how to use and manage Visual Studio Team Services (VSTS) and about the structure of the sample application used throughout the book. You will become familiar with the nitty gritty of Continuous Integration and Continuous Development with VSTS and Microsoft Azure Apps. You will not only learn how to create App service environments, but also how to compare Azure Web Apps and App Service Environments to deploy web applications in a more secure environment.Once you have completed Continuous Integration and created the Platform for application deployment, you will learn more about the final stepping stone in achieving end-to-end automation using approval-based Continuous Delivery and Deployment. You will then learn about Continuous Monitoring, using the monitoring and notification options provided by Microsoft Azure and Visual Studio Team Services.Style and ApproachThis book is an easy-to-follow guide filled with examples and real-world applications for gaining an in-depth understanding of Microsoft Azure and Visual Studio. This book will help you leverage Microsoft Azure and Visual Studio using real-world examples.